2016
DOI: 10.1017/s1751731115002232
|View full text |Cite
|
Sign up to set email alerts
|

Dairy goat kids fed liquid diets in substitution of goat milk and slaughtered at different ages: an economic viability analysis using Monte Carlo techniques

Abstract: The aim of this study was to analyze the economic viability of producing dairy goat kids fed liquid diets in alternative of goat milk and slaughtered at two different ages. Forty-eight male newborn Saanen and Alpine kids were selected and allocated to four groups using a completely randomized factorial design: goat milk (GM), cow milk (CM), commercial milk replacer (CMR) and fermented cow colostrum (FC). Each group was then divided into two groups: slaughter at 60 and 90 days of age. The animals received Tifto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…The decline in the selling price of goats is the most sensitive parameter in the Etawah dairy goat business in the Meunasah Mon Livestock Group. This is in line with what was conveyed by [11].…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…The decline in the selling price of goats is the most sensitive parameter in the Etawah dairy goat business in the Meunasah Mon Livestock Group. This is in line with what was conveyed by [11].…”
Section: Sensitivity Analysissupporting
confidence: 92%
“…Hassan et al ( 2018) evaluated goat's milk substitutes in raising Shami kids, kids fed with milk substitutes had higher final live weight (14.22 ± 0.2 kg vs 15.19 ± 0.3 kg; P <0.01) and average daily gain (120 ± 2g/day vs 130 ± 3g/day) compared to animals on natural lactation. Strategies for the use of milk substitutes in goat farming are important to make the goat product more available to the market, since its economic value is greater, as suggested by Knupp et al (2016).…”
Section: Resultsmentioning
confidence: 99%
“…For the carcass cost, the local market values in force in the experimental period (U$$ 7.02) were considered. Knupp et al (2016) found that the production of goats for slaughter is profitable and influenced by the sale price of the animals, the cost of the diet and the weight of the animals at slaughter. The same authors observed that bovine milk can and should be used in goat production systems as a way to cheapen the final product.…”
Section: Resultsmentioning
confidence: 99%